Citizen involvement in waste management and circular economy in cities: Key elements for planning and implementation - Izdebska, Olga; Knieling, Jörg (European Spatial Research and Policy, 2020)
This paper identifies and explores key elements for planning and implementing citizen involvement in the area of waste management and circular economy in cities. The analysis has shown that institutions responsible for waste management regard strategic planning, inclusivity, transparency, continuity, and resources as particularly important for reaching the objectives of citizen involvement. However, not all of the four analysed cities have applied these elements to the same extent, due to e.g. a lack of a strategy for citizen involvement, or limited personal and financial resources.